The Effectiveness of CLT Method in Improving English Students Ability in KSK Institute of Fathimatuzzahro - Suryanto, Bradhiansyah Tri; Nikmatillah, Ulfatul (International Journal of English Education and Linguistics (IJoEEL), 2020)
The aims of this study are to: 1) Investigate the English learning process by using the CLT method in KSK Institute of Fathimatuzzahro, Nurul Jadid Islamic Boarding School, 2) Investigate the effectiveness of the CLT method in improving students' English ability, 3) Investigate the perception of students of KSK Institute of Fathimatuzzahro, Nurul Jadid Islamic Boarding School on English language skills after participating in learning process by using the CLT method, 4) Investigate the supporting and inhibiting factors in increasing the effectiveness of the English learning process in KSK Institute of Fathimatuzzahro, Nurul Jadid Islamic Boarding School. Theories and concepts used include: CLT learning methods, and English communication skills. The method used in this research is descriptive method with a quantitative approach. Data collection techniques used in this research, namely questionnaire, interview, observation and test. The sample of this research is 70 students of KSK Institute of Fathimatuzzahro, Nurul Jadid Islamic Boarding School. Based on the results of data processing, it was obtained that the CLT Learning Methodgave significanteffect on the English communication skills. In general, the average value of the CLT learning method variable scores implemented in the learning process in KSK Institute of Fathimatuzzahro, Nurul Jadid Islamic Boarding School in upgrading English communication skills have high qualifications, score per aspect of students perceptions in KSK Institute of Fathimatuzzahro, Nurul Jadid Islamic Boarding School on students' English proficiency using the CLT learning method is in the high category and score of each aspects of supporting and inhibiting factors in increasing the effectiveness of the learning process English courses in KSK Institute of Fathimatuzzahro, Nurul Jadid Islamic Boarding School are in the high category.